The structure of the cutaneous pedal glands in the banded snail Cepaea hortensis (Müller, 1774). (3rd November 2017) - von Byern, Janek; Cyran, Norbert; Klepal, Waltraud; Rudoll, Livia; Suppan, Johannes; Greistorfer, Sophie
Abstract: Although gastropods have been crawling through the ocean and on the land for 60 million years, we still know very little about the sticky mucus produced in their foot. Most research has been focused on marine species in particular and, to a lesser extent, on the well‐known terrestrial species Arion vulgaris and Cornu aspersum . Within this study, we aim to characterize the foot anatomy of a smaller representative of the family Helicidae, the banded snail Cepaea hortensis . We are particularly interested in the microanatomy of the foot glands, their position, and the histochemical nature of their secretory content. Characterization of the dorsal foot region of Cepaea hortensis reveals four glands, differing in their size and in the granules produced. Histochemically, three of them react positively for sugars (PAS staining and lectin affinity tests for mannose, glucose and N ‐acetyl‐d ‐glucosamine) and acidic proteins (positive Alcian blue and Toluidine blue staining), indicating the presence of acidic glycosaminoglycans. The fourth gland type does not react to any of these dyes. The ventral pedal region includes two different gland types, which are positive for the presence of acidic glycoproteins, with a lectin affinity for mannose only. A comparison with Helix pomatia indicates differences regarding the number of glands and their contents. In Helix, only three gland types are described in the dorsal region of the foot, which show a similar granular appearance but nevertheless differ in their chemical composition. Congruently, there are two gland types in the ventral region in both species, whereas in Helix an additional sugar moiety is found. This raises the question whether these differences between the pedal glandular systems of both helicid species are the result of protection or size‐related adaptations, as they occur in the same habitat. Graphical Abstract Text: The microanatomy of the Cepaea hortensis pedal gland system is described for the first time. Histochemically, the glands mostly consist of acidic glycosaminoglycans containing sugars such as mannose, glucose, and N ‐acetyl‐d ‐glucosamine. The data given for Cepaea hortensis differ from those of related helicid species as Helix pomatia in regards to gland number and composition.